Small States as “Contributing Nations” to the EU’s Normative Power: the Case of Slovenia - Rok Zupančič; Miha Hribernik (Romanian Journal of European Affairs)
How can small states contribute to the overall normative power of the European Union (EU)? In this article we assess how much Slovenia, a small EU Member State with limited financial and human resources, contributes to this normative power. We do this by analysing its foreign policy, which consists of three main guiding principles: internationalism, the desire to solve all outstanding issues with its neighbour Croatia, and an attempt to present itself as a bridge between the EU and the Western Balkans. We discover that, while these principles exist on paper, they are often not consistently carried out in practice, which is a symptom of the stillongoing reorientation of the country’s foreign policy, after successfully joining the EU and the North Atlantic Treaty Organization (NATO) in 2004. Slovenian decision makers all too often remain reactive, and prefer to support the initiatives of others. When the country does act on its own initiative, its actions can be seen as too individualistic and uncoordinated, both within its own borders, and with its EU partners, as was the case when Slovenia launched the socalled Brdo Process, aimed at promoting cooperation between countries of former Yugoslavia. The conduct of Slovenian foreign policy is, all too often left, to the initiative and ingenuity of individuals, and such an uncoordinated approach hinders Slovenian efforts to become a normative power and to increase its influence in the Western Balkans. Finally, we argue that Slovenia’s Presidency of the EU Council in 2008 was a unique opportunity to contribute to the EU’s normative power. Slovenia managed to accomplish this only in part; despite the fact that the Presidency was an organisational success, most of its goals was too broadly defined and lacked ambition.